STRATEGIC TRADE POLICY UNDER PRESIDENT PRABOWO: A NARRATIVE REVIEW OF INDONESIA’S GVC RESPONSE - Wijaya, Andy; Sisca, Sisca; Simarmata, Hengki Mangiring Parulian (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
This research examines Indonesia's strategic reaction to global value chain (GVC) disruptions via export tariff reforms under President Prabowo Subianto's administration. This research utilises a narrative literature analysis to combine findings from peer-reviewed journals, policy documents, and institutional reports published from 2014 to 2024. The study reveals that whereas tariff liberalisation seeks to improve export competitiveness, its efficacy is limited by non-tariff barriers, deficiencies in digital infrastructure, and institutional fragmentation. Compared to regional counterparts like Vietnam and Thailand, Indonesia's inward-oriented trade policy may restrict its inclusion into high-value areas of global value chains. The investigation is confined to secondary sources, providing conceptual insights instead of causal assertions. It underscores the necessity for synchronised reforms, including logistical modernisation, digital preparedness, and conformity with environmental, social, and governance (ESG) criteria. This study enhances the discussion on trade policy adjustment in emerging economies in the context of increasing global uncertainty